Analisis Faktor-Faktor Yang Mempengaruhi Perilaku Wajib Pajak Dalam Penggunaan E-Filing - Sylvia, Ngadiman (Fakultas Ekonomi, Universitas Tarumanagara, 2019)
This research aims to obtain empirical evidence usefullness of e-filing, ease of use of e-filing, security and privacy of using e-filing on actual usage of e-filing on individual taxpayers in the West Jakarta area. The sample in this study were 100 respondents of individual taxpayers. The results of this study indicate that the usefullness of e-filing has a significant influence on the use of e-filing, while ease of use, security and privacy do not have a significant effect on the use of e-filing